Amelioration of oxidative DNA damage in mouse peritoneal macrophages by Hippophae salicifolia due to its proton (H+) donation capability: Ex vivo and in vivo studies - Mainak Chakraborty; Indrajit Karmakar; Sagnik Haldar; Avratanu Das; Asis Bala; Pallab Kanti Haldar (Wolters Kluwer Medknow Publications, 2016)
Introduction: The present study evaluates the antioxidant effect of methanol extract of Hippophae salicifolia (MEHS) bark with special emphasis on its role on oxidative DNA damage in mouse peritoneal macrophages. Material and Methods: In vitro antioxidant activity was estimated by standard antioxidant assays whereas the antioxidant activity concluded the H+ donating capacity. Mouse erythrocytes' hemolysis and peritoneal macrophages' DNA damage were determined spectrophotometrically. In vivo antioxidant activity of MEHS was determined in carbon tetrachloride-induced mice by studying its effect on superoxide anion production in macrophages cells, superoxide dismutase in the cell lysate, DNA damage, lipid peroxidation, and reduces glutathione. Results: The extract showed good in vitro antioxidant activities whereas the inhibitory concentrations values ranged from 5.80 to 106.5 μg/ml. MEHS significantly (P < 0.05) attenuated the oxidative DNA damage. It also attenuated the oxidative conversion of hemoglobin to methemoglobin and elevation of enzymatic and nonenzymatic antioxidant in cells. Conclusion: The result indicates MEHS has good in vitro-in vivo antioxidant property as well as the protective effect on DNA and red blood cell may be due to its H+ donating property.